Effectiveness of the use of spiritual intelligence in women academic leadership practice - Ramachandaran, Sharmila Devi; Krauss, Steven Eric; Hamzah, Azimi; Idris, Khairuddin (Emerald Publishing, 2017)
Purpose – The purpose of this paper is to explore the effectiveness of the use of spiritual intelligence into women academic leadership practices. The study designed to provide a clear understanding of the effectiveness of the use of spiritual intelligence practices within women academic leadership practices. In addition, the study will be an ideal for women in academic environment, considering that more women will have the opportunities to hold leadership positions in higher learning institutions. Understanding the unique skills and attributes of spiritual intelligence could increase their confidence towards taking on leadership positions in future. This study will also provide greater clarification on how spiritual intelligence when translated through leadership practice will contribute to a more balanced and harmonious working environment. Design/methodology/approach – The study assimilated a qualitative approach guided by phenomenological inquiry to explore the effectiveness of the use of spiritual intelligence practices among the women leaders. Phenomenology best fit the researchers’ assumptions that it is possible to know, define and categorize women academic leader’s experiences in a more structured manner. It is by entering into their field of perception that the researcher pursues to understand spiritual intelligence as the leaders saw it. Findings – The finding established three main effectiveness of integrating spiritual intelligence into leadership practices: employees inspired by vision; increase credibility and long-term sustainability of institution; and heightened moral values and reduces ethical issues. The authors conclude that bringing the attributions of spiritual intelligence will transform the workplace into a more meaningful and purposeful atmosphere by constructing balanced and harmonious relationship within employees. Research limitations/implications – The study rely profoundly on women academic leaders as a primary source of data. Due to their higher position, there may be some elements of their works which are similar to each other or different compared with other women leaders who may not have reached the higher position. The responses was mainly based on the self-perception of women academic leaders grounded on their insight of leadership and experience. This experiences probably could not be verified by others to see if their perceptions of leadership were in line with how others perceive them. The study also limited in terms of generalizability as the sample was purposively selected. Practical implications – The study will be applicable for human resource personnel to develop policies and procedures that are needed to improve the holistic strategies of leading not only in public university but also throughout all the other higher educational institutions. The study assist researcher and the practitioner in the Human Resource Development (HRD) field to understand the issues related to leadership practice in current era. Hence, the information in this study could be used to aid them in advocating employee training programs and formulating HRD intervention remedial programs input for designing and facilitating of intervention for professional academic leaders, academicians and change agent to understand and analyse the characteristics of personal and organizational situation in order to contribute to the long run survival of the higher educational learning institutions. Originality/value – This paper has provided unique evidence of women leadership particularly in Malaysian higher educational context on their experiences of spiritual intelligence and its effectiveness into their leadership practices.